2022
DOI: 10.3390/v14051001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Pathogenesis of H6N6 Low Pathogenic Avian Influenza Viruses Isolated from Mallard Ducks (Anas platyrhynchos) in South Korea

Abstract: The subtype H6N6 has been identified worldwide following the increasing frequency of avian influenza viruses (AIVs). These AIVs also have the ability to bind to human-like receptors, thereby increasing the risk of animal-human transmission. In September 2019, an H6N6 avian influenza virus—KNU2019-48 (A/Mallard (Anas platyrhynchos)/South Korea/KNU 2019-48/2019(H6N6))—was isolated from Anas platyrhynchos in South Korea. Phylogenetic analysis results revealed that the hemagglutinin (HA) gene of this strain belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In September 2019, an H6N6-AIV (KNU2019-48) was isolated in South Korea, which was the first reported AIV in Korea. In fact, the H6-subtype viruses had co-circulated in China, Vietnam, and Korea for half a decade ( Durairaj et al, 2022 ). Therefore, the monitoring and prevention of the H6-subtype AIVs, especially H6N6 subtype, should not be taken lightly.…”
Section: Discussionmentioning
confidence: 99%
“…In September 2019, an H6N6-AIV (KNU2019-48) was isolated in South Korea, which was the first reported AIV in Korea. In fact, the H6-subtype viruses had co-circulated in China, Vietnam, and Korea for half a decade ( Durairaj et al, 2022 ). Therefore, the monitoring and prevention of the H6-subtype AIVs, especially H6N6 subtype, should not be taken lightly.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a study found that PB2-E627K enhanced the replication of the H6N1 virus in mammals [ 41 ]. Other mutations: Kaliannan Durairal et al identified PB1 (S375N/T) and PA (A404S, S409N) human host markers in the genes of KNU2019-48 (H6N6) isolates [ 42 ], which may contribute to the adaptation of H6 subtype AIVs to mammals. Furthermore, although amino acid mutations that have been previously shown to be associated with receptor preferences for other AIV subtypes have been identified in H6 AIV, where a small number of results have been based only on currently published AIV human host markers and have not been validated in animal studies, so further investigation is needed to clarify the relationship between these mutations and H6 AIV human receptor preferences.…”
Section: Molecular Characterization Of Surface Genes and Inner Genesmentioning
confidence: 99%
“…However, in recent years, M2-S31N and M2-V27I mutations have been found in some strains that are resistant to amantadine [ 25 , 45 ]. Mutant residues E119V, H275Y, R293K and N295S were found in the H6 AIV NA origin gene of Korean Anas platyrhynchos , indicating resistance to oseltamivir [ 42 ]. However, several H6 subtype AIV isolates have also been found to be susceptible to oseltamivir [ 46 ], so enhanced monitoring of the resistance of H6 subtype AIV against NA inhibitor drugs is needed to precisely select targeted antiviral drugs for efficient treatment.…”
Section: Molecular Characterization Of Surface Genes and Inner Genesmentioning
confidence: 99%